Risk analysis for groundwater in the area of the municipal waste landfill in Sosnowiec, South Poland - Bareła Natalia; Dąbrowska Dominika (Environmental & Socio-economic Studies, 2024)
Risk assessment for groundwater allows for preventive activities in the field of environmental monitoring. The risk assessment for groundwater in the area of the municipal waste landfill in Sosnowiec was carried out using the Nemerov Index (NPI) and the Enrichment Index (EF), as well as a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and a risk matrix. It was performed on the basis of the database from 2014-2019 for ten piezometers belonging to the landfill’s observation network. In the case of the risk matrix, 20 risks were identified regarding climatic conditions, landfill infrastructure and employees. The SWOT analysis considered the strengths and weaknesses of the facility as well as opportunities related to technological development and threats related primarily to the location of the facility within the landscape. The risk assessment indices were calculated for the following parameters: electrolytic conductivity, Na, Mg, K, Ca, Mn, Fe, TOC, HCO3, Cl, SO4, and NH4. The highest values of the NPI index exceeded 3,500 (in a single measurement), while for the EF index the values reached almost 500. These prove the impact of this facility on the quality of groundwater. However, hydrochemical background value and the value of the immobile parameter are also important. This article uses limit values for the first class of groundwater quality. The results of above mentioned methods indicate a medium risk to groundwater, and the opportunities and strengths of the facility outweigh the negative aspects of the plant’s operation. Further research should include the identification of additional risk factors and the likely response to risk.